Pengaruh pandemi Covid-19 terhadap indeks sektoral di Bursa Efek Indonesia - Basis G Andamari; Shanti Lysandra; Salis Musta Ani (LPMP Imperium, 2022)
This study analyzes the effect of the Covid-19 pandemic, which consists of the number of confirmed positives, the number of active people, and the number who died from Covid-19 on the sectoral index on the Indonesia Stock Exchange (IDX). The research method used is quantitative research with causality analysis. The data used in this study is secondary data obtained from the Ministry of Health website and Worldometers for the Covid-19 pandemic and the IDX for sectoral index data for the period January 2020-June 2021. The results of the analysis show that the Covid-19 pandemic affects all IDX sectoral indices with a high level of different influences, namely: (1) significantly negatively affected sectors: properties and trade (transportation, restaurant, hotel, and leisure sub-sectors), (2) negatively affected sectors: miscellaneous industry, consumer, financial and manufacture and ( 3) Positively affected sectors: mining and infrastructure (telecommunication and technology sub-sector).